2019
DOI: 10.3390/economies7030065
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Inclusive Growth Policy

Abstract: Background: Since the latter part of the 20th Century, countries have been particularly challenged by the trade-off that exists between delivering generous welfare provisions and strong economic growth. Such dynamics have stimulated a need to better understand the causes of income inequality so as to better formulate policies that foster inclusive growth and reduce growing concerns surrounding income inequality. Method: Given its ability to succinctly summarize, analyze, and synthesize an extant body of litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…This is in the line of Picketty's analysis of the process of increasing inequality [24]. At this level, one study [25] identified four key areas that decrease income inequality in both developed and developing economies: (i) technological change-oriented skills; (ii) the improvement of educational systems; (iii) the consolidation of globalisation; and (iv) labor market reforms.…”
Section: Academic Literaturementioning
confidence: 89%
“…This is in the line of Picketty's analysis of the process of increasing inequality [24]. At this level, one study [25] identified four key areas that decrease income inequality in both developed and developing economies: (i) technological change-oriented skills; (ii) the improvement of educational systems; (iii) the consolidation of globalisation; and (iv) labor market reforms.…”
Section: Academic Literaturementioning
confidence: 89%
“…Our decision to focus on this topic reflects both the importance of effective waste management practices and their implications for indigenous people. An integrative literature review is a specific form of research that seeks to not only categorize information about a particular area of study, but also to create new knowledge about topics reviewed (Torraco, 2005(Torraco, , 2016; Heshmati et al, eTropic: electronic journal of studies in the tropics ; Wood et al, 2020). Furthermore, literature reviews are an effective means of succinctly summarizing and critically analyzing an extant body of literature from a particular field of study (Chermack & Passmore, 2005).…”
Section: Methodological Approachmentioning
confidence: 99%
“…This trade-off decision had not only reduced the cost but also enhanced social connectivity and opened doors to better education, employment, and businesses for the neglected backward regions of the Balochistan province. Similarly, (Heshmati et al 2019) took the case of challenged trade-offs between welfare and economic growth and argued that there is a need for better understanding of the causes of income inequality.…”
Section: Trade-offs and Social Impacts Of Transportationmentioning
confidence: 99%